Cultural Participatory in Tourism Digital Marketing Communication Channel - Riris Loisa; Diah Ayu Candraningrum; Lusia Savitri Setyo Utami; Lydia Irena (Jurnal Komunikasi, 2021)
Tourism is one of Indonesia's leading sectors that has been seriously affected by the pandemic. This study aims to describe participatory culture in digital tourism marketing communication channels during the pandemic, through Instagram social media channels from micro-influencers, that focus on three priority tourism destinations that have been set by the government. By using the Participatory Media Culture Theory from Henry Jenkins, it is further studied how consumers and producers create cultural artifacts with commodity value. The research applied a netnographic method, the data were gathered and analyzed by the social media analysis application Analysis.io. The subject of research is the influencers and followers in 3 (three) Instagram accounts: @explorejogja, @indraseptianazhari, and @travelwithgerie, while the object of the research was the forms of participation as cultural artifacts in these accounts This study concludes that the participants build a participatory culture by the power of visual and narrative artifacts, as well as their spreadability. Further this research shows that (1) cultural artifacts in each account have their own characteristics, with similarities in the prosumer participation, where reposting becomes a cultural artifact that has its own power to form virtual relationships; (2) attractive visuals and informal guides in the form of narratives are also cultural artifacts that invite further involvement of participants, in the form of likes, comments, reposts, etc.; and (3) the presence of micro-influencers who are inherently intertwined with these accounts jointly contributing to the dissemination of content and their respective accounts, which in turn becomes a force for the spread of tourism marketing, especially during the pandemic. Pariwisata adalah salah satu sektor unggulan Indonesia yang terkena dampak serius dari pandemi ini. Penelitian ini bertujuan untuk mendeskripsikan budaya partisipatif dalam saluran komunikasi pemasaran pariwisata digital selama pandemi, melalui saluran media sosial Instagram dari mikro-influencer, yang berfokus pada tiga destinasi wisata prioritas yang telah ditetapkan oleh pemerintah. Dengan menggunakan Teori Budaya Media Partisipatif dari Henry Jenkins, lebih lanjut dipelajari bagaimana konsumen dan produsen menciptakan artefak budaya dengan nilai komoditas. Penelitian ini menggunakan metode netnografi, data dikumpulkan dan dianalisis dengan aplikasi analisis media sosial Analysis.io. Subjek penelitian adalah influencer dan followers di 3 (tiga) akun Instagram: @explorejogja, @indraseptianazhari, dan @travelwithgerie, sedangkan objek penelitian adalah bentuk partisipasi sebagai artefak budaya dalam akun tersebut. Penelitian ini menyimpulkan budaya partisipatori dibangun dengan kekuatan artefak visual dan naratif, serta daya sebarnya. Lebih lanjut, penelitian ini menunjukkan bahwa (1) artefak budaya di setiap akun memiliki ciri khas tersendiri, dengan kesamaan berupa partisipasi prosumer, dimana reposting menjadi artefak budaya yang memiliki kekuatan untuk membentuk hubungan virtual; (2) visual yang menarik dan panduan informal berupa narasi juga merupakan artefak budaya yang mengundang keterlibatan peserta lebih lanjut, dalam bentuk ekspresi rasa suka, komentar, repost, dll; dan (3) kehadiran micro-influencer yang secara inheren terjalin dengan akun-akun tersebut secara bersama-sama berkontribusi dalam penyebaran konten dan akunnya masing-masing, yang pada akhirnya menjadi kekuatan bagi penyebaran pemasaran pariwisata, khususnya di masa pandemi.